Karte der Far-Oer 1:100 000 (zu Danemark) (1940)
Relief indicated by contours and spot heights; depths by soundings. "Sonderausgabe!" Nur fur den Dienstgebrauch! In Faeroese, Danish, and German. Color; 1:100,000.